(untitled) (Research, Society and Development, 2021)
Motivation in learning is very influential in the learning outcomes of each student. The level of motivation to learn is one of the factors that play an important role in increasing one’s interest in learning. In this study the researcher tried to see the impact of using verbal and written feedback on individual motivation and interest in learning. This research was conducted descriptively with qualitative methods. Related qualitative researches are used to assist in describing common elements of various forms. Descriptive qualitative research aims to investigate detailed descriptions of people, places, or events in a setting in a qualitative approach. Data were collected from questionnaires and interviews which were distributed to 30 students of the University of Muslim Nusantara Al-Washliyah, Medan. From the results of the study, it can be concluded that the formative type of feedback is the most chosen type by students and the type of feedback from oneself that is the least chosen. One point here is that feedback is not usually neutral - it often triggers a positive or negative emotional response. In this research, we discuss positive feedback because there is no negative feedback. From the results it can be seen that the positive feedback given by the lecturer can increase student motivation. It can be seen from the interviews that have been conducted and the responses during teaching and learning in class. There is enthusiasm from students in interacting at the end of the lesson.